Rainfall interception and redistribution by maize farmland in central Iran - Mahtab Nazari; Seyed Mohammad Moein Sadeghi; John Toland Van Stan, II; Mohammad Reza Chaichi (Journal of Hydrology: Regional Studies, 2020)
Study region: Maize farmland in Varamin, located southwest of Tehran (Iran). Study focus: The aims of this study were to: (1) monitor throughfall and stemflow during rainstorms beneath maize canopies over two growing seasons (2015, 2016); (2) evaluate the effect of maize canopy structure (leaf area index, plant height) on throughfall, stemflow, and interception; and (3) develop an analytical model of rainfall partitioning by maize from controlled rainfall simulations. New hydrological insights for the region: Rainfall or irrigation interception by crops and residues has often been overlooked in hydrologic modelling in Iran. However, our results confirm that interception by maize canopy can significantly reduce total water input to the surface (19.9 % and 11.2 % of natural and simulated rainfalls, respectively). Although rainfall amounts and rates were similar between simulations and natural rainfall, differences in interception value may still exist between simulated and natural conditions due to the formation, size distribution, and movement of water droplets emitted from simulation systems vs. natural rainfall water droplets. Throughfall and interception significantly correlated with LAI and height of the maize canopy above thresholds of 2.5 (LAI) and 180 cm (height). The analytical model performed well under natural rain conditions. These results may help farmers’ irrigation scheduling achieve higher irrigation water use efficiency for maize fields, particularly in arid agricultural lands. Keywords: Arid region, Leaf area index, Plant height, Rainfall intensity, Rainfall magnitude